Peningkatan Kapasitas Karang Taruna Kabupaten Barru Sebagai Mitra Pemerintah Desa Dalam Fungsi Pengawasan Pembangunan - Didin Halim; Aditya Sulthony Ahmad Khan; Ahmad Difa Awlia Aslim; Tri Cahyo Nugroho; Irfan. B (DEDIKASI, 2026)
Abstract. Karang Taruna is a youth organization that plays a strategic role in supporting village development through active community participation. However, the institutional capacity and technical competencies of Karang Taruna organizations in Barru Regency still face various challenges, particularly in carrying out development oversight functions. This community service program aimed to strengthen the capacity of Karang Taruna as a partner of village governments in monitoring and supervising village development. The methods employed included socialization, training, mentoring, digital technology implementation, and the development of a sustainability strategy. The training covered organizational governance, youth leadership, participatory village development monitoring, administrative management, and the utilization of information technology for reporting and transparency. The results demonstrated an improvement in the knowledge and skills of Karang Taruna members regarding village development mechanisms, participatory monitoring practices, and systematic reporting procedures. Furthermore, the program successfully enhanced collaboration between Karang Taruna and village governments in promoting more transparent, participatory, and accountable development governance. Program sustainability was supported through the establishment of village monitoring teams, the development of institutional partnerships, and the provision of participatory development monitoring guidelines. Therefore, Karang Taruna in Barru Regency has strengthened its potential to serve as a social control agent and a strategic partner of village governments in fostering sustainable development.Keywords: Karang Taruna, village development oversight, youth empowerment, institutional capacity, community participation, Barru Regency.